2017
DOI: 10.1021/acs.macromol.7b01786
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Chain Architecture and the Presence of End-Groups or Branching Units Chemically Different from Repeating Structural Units on the Critical Adsorption Point in Liquid Chromatography

Abstract: The critical adsorption point (CAP) of linear and star-shaped polymers was investigated by normal phase and reversed phase liquid chromatography (NPLC and RPLC) and computer simulation. Three sets of polystyrenes (PS) differing in chain architecture and chemically distinct groups were prepared: linear PS (sec-butyl and hydrogen end group), 2-arm PS (linear, two sec-butyl end groups and one silyl group in the middle of the chain) and 4-arm star-shaped PS (four sec-butyl end groups and one silyl group in the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Most of the recent molecular simulation studies employed MD to examine the retention process in RP-HPLC. , These calculations yield a microscopic picture of the local structure and dynamics of the RP-HPLC interface on an atomic scale. In a typical model of a chromatography system, a periodic boundary condition with a particular unit cell dimension (e.g., 40 × 40 × 80 Å) is applied to generate a mimic of each molecular model, which consists of four parts: silica support, ligands (i.e., alkyl chains) with a particular surface coverage, solvent molecules (e.g., water/methanol mixture), and solutes.…”
Section: Application Of Molecular Simulations In Rp-hplcmentioning
confidence: 99%
“…Most of the recent molecular simulation studies employed MD to examine the retention process in RP-HPLC. , These calculations yield a microscopic picture of the local structure and dynamics of the RP-HPLC interface on an atomic scale. In a typical model of a chromatography system, a periodic boundary condition with a particular unit cell dimension (e.g., 40 × 40 × 80 Å) is applied to generate a mimic of each molecular model, which consists of four parts: silica support, ligands (i.e., alkyl chains) with a particular surface coverage, solvent molecules (e.g., water/methanol mixture), and solutes.…”
Section: Application Of Molecular Simulations In Rp-hplcmentioning
confidence: 99%
“…In addition to the findings and explanations of Ahn et al, also the influence of additional end-groups in the branched chains might be considered. Radke et al and Biela et al demonstrated the influence of the local distribution of functional (end-)­groups along the polymer chain on the elution behavior in LCCC.…”
Section: Resultsmentioning
confidence: 99%
“…The exceptional elution behavior might be explained by a combination of the influence of architecture and end-groups of the branched polymer chains. Ahn et al 50 observed a SEC elution for 4-arm star-shaped PS at the critical conditions of linear PS in NPLC. Interestingly, the same 4-arm star-shaped PS eluted in "pseudo-SEC" mode at the critical conditions of linear PS in RPLC; however, the 4-arm star-shaped PS eluted at volumes, which would be indicative for LAC elution.…”
mentioning
confidence: 99%
“…They enable checking of the correctness of theoretical hypotheses and predictions and provide data that are either inaccessible or barely accessible by experiments. Furthermore, in combined experimental and theoretical research, they offer a relatively fast and cheap substitute for a substantial part of the tedious and expensive experimental work [90][91][92][93][94]. Thanks to enormous progress in computer technology, atomistic simulations (even quantum simulations) of relatively large systems, such as enzymes and catalytic or biocatalytic centres, have become feasible in recent decades [95][96][97][98][99].…”
Section: Coarse-grained Computer Modelling Of Polymer Chainsmentioning
confidence: 99%